Reconceptualizing Islamic Religious Character Education: A Theoretical Framework for National Character Formation - Haniefa Nuruddienil Fithriy; Dewi Churiah; Laila Julistiqomah; Muhammad Thufaili Ubaidillah (Journal of Elementary Education Research and Practice, 2026)
This study examines Islamic religious character education as a conceptual framework for national character formation through a qualitative, theory-driven library research approach. Drawing on Islamic educational thought and engaging with contemporary character education theories advanced by Lickona, Bandura, and Kohlberg, the study analyzes how moral internalization, pedagogical practices, and spiritual accountability shape ethical behaviour and civic virtue. The findings indicate that Islamic religious character education converges with established character education frameworks in its emphasis on moral cognition, modelling, and habituation, while extending them by integrating spiritual accountability as a sustained source of moral motivation. In pluralistic societies, religious character education, when grounded in inclusivity and moderation, supports national civic virtues such as justice, tolerance, social responsibility, and respect for human dignity. This study contributes to international debates on character education by positioning Islamic religious character education as a theoretically relevant and context-sensitive resource for national character formation. Future studies are encouraged to empirically explore how inclusive models of religious character education are implemented across diverse educational settings and their implications for educational policy and practice.